Foundations of Atlas: Rapid Ajax Development with ASP.NET 2.0 - Moroney, Laurence (Apress, 2012)
Ajax is fast becoming the buzzword in web development for 2006. It’s also becoming a de facto standard for developing user-centric web applications. It’s an evolutionary step in the user experience and is being used in more and more web applications from Google Local maps to Live.com to Amazon and beyond. But how do you write Ajax applications? You’ve got to be a JavaScript expert and use tools that are not as sophisticated as those your C# or Java friends use. As such, it can be difficult and time-consuming to develop, debug, and maintain Ajax applications despite their innate user friendliness. Microsoft is contributing to the solution for this problem with its Atlas framework. This builds on top of the best-of-breed ASP.NET technology and Visual Studio 2005 integrated development environment (IDE) to bring major productivity leaps to Ajax development. With Atlas you can easily convert your existing ASP.NET applications to Ajax ones, and you can add sophisticated user interface elements such as drag and drop, networking, and browser compatibility layers with simple declarative programming (or, if you prefer to use JavaScript, you can do that too).